Exploring sauna impulse responses - Prawda, Karolina; Meyer-Kahlen, Nils; Schlecht, Sebastian (INTER-NOISE and NOISE-CON Congress and Conference Proceedings, 2024)
Sauna is an important element of Finnish tradition and culture, and its properties and features deserve preservation and archiving. Additionally, extreme temperature and humidity in a sauna comprise a unique environment for researching room acoustics in unusual atmospheric conditions. In the present study, we publish a dataset of room impulse response (RIR) measurements of a sauna during the process of warming up and throwing water on the stove. We explore several features of the dataset, such as the impact of the temperature and humidity distributions on the time-of-arrival of reflections, the atmospheric absorption of sound, and spectral coloration of measured RIRs. The results of this research show the influence of environmental factors on RIRs and allow an insight into the distinct room acoustics of a sauna while heating u